IDENTIFICATION OF FRUIT FLY (DIPTERA: TEPHRITIDAE) IN SEVERAL DISTRICTS IN NORTH SUMATERA - Humayra Windayani Rangkuti; Nurhayati; Rahmad Setia Budi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Humayra Windayani Rangkuti, Identification of Fruit Flies (Diptera: Tephritidae) in Several Districts in North Sumatra Province. Supervised by Prof. Dr. Ir. Nur Hayati, MP and Dr. Ir. Rahmad Setia Budi, M.Sc. Fruit flies (Diptera: Tephritidae) are one of the economically important pests that attract world attention. Fruit flies are generally polyphagous with a wide host range. The presence of fruit flies is a limiting factor for the export of agricultural products, especially fruits and vegetables. Fruits infested with fruit flies will rot and their growth will become abnormal. The damage caused can reach 90%-100%. Sampling of fruit flies using the collection method of trapping using a lure or attractant Methyl eugenol (ME). The study was conducted in several districts in the North Sumatra Region. Fruit flies were identified at the Integrated Laboratory of the North Sumatra Animal, Fish, and Plant Quarantine Center (BBKHIT Sumut). The research was conducted from May to December 2024. The results of the trap installation found 8 species of fruit flies of the genus Bactrocera, subgenus Bactrocera and Zeugodacus with the names of the species found being B. carambolae, B. dorsalis, B. albistrigata, B. (Zeugodacus) tau, B. umbrosa, B. (Z.) caudata, B. raiensis, B. verbasifolie, B. (Z.) cucurbitae. Information on species and status of fruit flies in North Sumatra can be used as a reference in anticipating the spread of fruit flies and how to control them on agricultural products with high economic value. Making a list of pest species (pest list) and description of morphological characteristics of OPT, especially fruit flies, is important in trade negotiations. One of the important roles of quarantine is to prevent the entry and exit of OPT/OPTK including fruit flies from one country to another or from one area to another within the country, or out of the territory of the Republic of Indonesia through local and international trade activities.